PENGARUH KUALITAS PELAYANAN PAJAK, SANKSI PAJAK DAN KESADARAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK BUMI DAN BANGUNAN (STUDI KASUS PADA KABUPATEN ACEH UTARA) - Azia Kausarina; Nuraini Nuraini; Yulia Fitri (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2021)
The purpose of this study was to determine the effect of service quality, tax sanctions and awareness by taxpayers on taxpayer compliance in paying land and building taxes. Data collection techniques in this study were carried out by distributing questionnaires containing statements with available alternative answers to Land and Building Taxpayers in North Aceh. The data analysis method used is multiple linear regression analysis. Research data processing is done by using SPSS software model for windows. The results of the study indicate that the variables of local government service quality, tax sanctions and taxpayer awareness simultaneously or partially have a significant and significant effect on taxpayer compliance in paying land and building taxes.